Microbially-mediated fugitive gas production from oil sands tailings and increased tailings densification rates. Issue 3 (1st May 2003) - Fedorak, P M; Coy, D L; Dudas, M J; Simpson, M J; Renneberg, A J; MacKinnon, M D
Abstract : Oil sands in northeastern Alberta, Canada, are strip mined and bitumen is separated from sand and clay by an alkaline hot water extraction process leaving millions of cubic metres of tailings for disposal. These include mature fine tailings (MFT) collected in settling ponds and consolidated or composite tailings (CT) that are produced by the addition of sand and gypsum to hasten dewatering and densification. This laboratory investigation monitored the potential for fugitive gas production in 0.9-m high columns that contained MFT or CT samples from three oil sands companies. Methane was found in columns that contained aged MFT, but not in those that contained fresh MFT. Dissolved or entrapped methane was found in columns containing each of the MFT samples and two of the CT samples. Ethylene was detected in columns containing MFT or CT. This may affect future plans to re-vegetate disturbed areas of the oil sands operations because ethylene strongly influences many phases of plant development. The densification rate of a methanogenic MFT was faster than that of a nonmethanogenic MFT that was placed in a similar column 6 years prior to the start of this investigation, suggesting that methane formation may increase the rate of densification. Key words: consolidated tailings, composite tailings, densification, ethylene, methane, methanogens, oil sands, sulfate-reducing bacteria.